New or rare Madagascar tiger beetles—20. Pogonostoma (Bathypogonum) horimichioi sp. nov. and supplemented characters of P. (B.) levigatum levigatum (W. Horn) and P. (B.) levigatum lucens Rivalier (Coleoptera: Cicindelidae) - Razanajaonarivalona, Elysé Hugo; Moravec, Jiří; Rakotomanana, Hajanirina (Zootaxa, 2021)
Pogonostoma (Bathypogonum) horimichioi sp. nov. is described as new to science from western Madagascar. Apart from a detailed description, illustrations in colour photographs of the habitus, diagnostic characters and habitat of the new species are introduced. A rectified differential diagnosis of the subgenus Bathypogonum Jeannel, 1946 is performed. The new species is compared to other two hitherto known taxa of the subgenus Bathypogonum (in its narrow original concept and sensu Moravec 2007), which are P. (B.) levigatum levigatum W. Horn, 1908 and P. (B.) levigatum lucens Rivalier, 1970. Differential diagnoses of the two taxa with illustrations of their habitus and important distinguishing characters in colour photographs are presented. References to their detailed redescriptions and illustrations, as well as to those of the subgenera Neopogonum Moravec, 2007 and Parapogonum Moravec, 2007 in the monograph of the genus Pogonostoma by Moravec (2007) are given. Essential maps of distribution are also presented.